Adverse childhood experiences and fronto-subcortical structures in the developing brain - Buimer, Elizabeth E. L.; Brouwer, Rachel M.; Mandl, René C. W.; Pas, Pascal; Schnack, Hugo G.; Hulshoff Pol, Hilleke E. (Frontiers in Psychiatry, 2022)
The impact of adverse childhood experiences (ACEs) differs between individuals and depends on the type and timing of the ACE. The aim of this study was to assess the relation between various recently occurred ACEs and morphology in the developing brain of children between 8-11 years of age. We measured subcortical volumes, cortical thickness, cortical surface area and fractional anisotropy in regions of interest in brain scans acquired in 1184 children from the YOUth cohort. ACEs were based on parent-reports of recent experiences and included: financial problems; parental mental health problems; physical health problems in the family; substance abuse in the family; trouble with police, justice or child protective services; change in household composition; change in housing; bereavement; divorce or conflict in the family; exposure to violence in the family and bullying victimization. We ran separate linear models for each ACE and each brain measure. Results were adjusted for the false discovery rate across regions of interest. ACEs were reported for 83% of children in the past year. Children were on average exposed to two ACEs. Substance abuse in the household was associated with larger cortical surface area in the left superior frontal gyrus, t(781) = 3.724, pFDR = .0077, right superior frontal gyrus, t(781) = 3.409, pFDR = .0110, left pars triangularis, t(781) = 3.614, pFDR = .0077, left rostral middle frontal gyrus, t(781) = 3.163, pFDR = .0195 and right caudal anterior cingulate gyrus, t(781) = 2.918, pFDR = .0348. Household exposure to violence (was associated with lower fractional anisotropy in the left and right cingulum bundle hippocampus region t(697) = -3.154, pFDR = .0101 and t(697) = -3.401, pFDR = .0085, respectively. Lower household incomes were more prevalent when parents reported exposure to violence and the mean parental education in years was lower when parents reported substance abuse in the family. No other significant associations with brain structures were found. Longer intervals between adversity and brain measurements and longitudinal measurements may reveal whether more evidence for the impact of adverse childhood experiences on brain development will emerge later in life.